Structure of the Surface Region of Stainless Steel: Bulk and Thin Films. Issue 4 (18th February 2022) - Garai, Debi; Wilson, Axel; Carlomagno, Ilaria; Meneghini, Carlo; Carla, Francesco; Hussain, Hadeel; Gupta, Ajay; Zegenhagen, Jörg
Abstract : The surface region of austenitic stainless steel (SS) is investigated by synchrotron X‐ray powder diffraction (XRPD) and X‐ray absorption near edge structure (XANES) measurements, because its composition and structure are crucial for the corrosion resistance of SS. Grazing incidence XRPD of a polished AISI 304 bulk steel sample shows that the near‐surface structure is modified. The concentration of the ferrite phase of Fe, a typical minority phase in AISI 304, increases gradually from 10% to 30% when approaching the surface from 150 nm depth. XANES Fe K‐edge investigations of ultrathin, sputter‐deposited films also reveal much larger ferrite fractions than expected from the austenitic steel composition of the films. Reasons for the increased ferrite fraction in the surface region of bulk steel and thin films are discussed. However, right at the surface, the trend reverses. Analysis of XANES data for an ultrathin, 4 nm SS film shows that 80% of Fe is oxidized and 20% of metallic Fe is present only in austenite structure, suggesting that ferritic iron is preferentially subject to oxidation. The austenitic Fe is located at more than 2–3 nm below the surface where the Ni concentration is >10%. Abstract : In stainless steel (SS), the local austenite/ferrite distribution determines mechanical properties such as hardness and, close to the surface, affects the corrosion resistance. X‐ray diffraction and near‐edge absorption analysis of bulk AISI 304 SS and thin films show that the concentration of ferrite, typically a typical minority phase in SS, strongly increases closer to the surface.